Effects of multiple pro-inflammatory stimuli in utero on the ileum of extremely premature ovine fetuses - Heiter, Julia; Kemp, Matthew W.; Spiller, Owen B.; Singer, Dominique; Newnham, John P.; Kallapur, Suhas G.; Jobe, Alan H.; Kramer, Boris W. (Frontiers in Immunology, 2023)
Introduction: Chorioamnionitis is common in preterm birth and associated with a higher risk of intestinal inflammation and necrotizing enterocolitis. The intestinal inflammation influences the enteric nervous system development. We hypothesized that inflammation and innervation in the fetal ileum may be modified by chorioamnionitis induced by repeated challenge with lipopolysaccharide and/or preexisting Ureaplasma parvum infection at very low gestational age equivalent to 60% of term. Materials and Methods: Time mated ovine fetuses were exposed by intraamniotic injections to chronic Ureaplasma parvum for 24 days and/ or lipopolysaccharide for 7 days, 2 days, or 7 & 2 days before delivery at 94 ± 2 days of gestational age (term at approximately 150 days). Intestinal inflammation as well as structural changes of the enteric nervous system were assessed. Results: Lipopolysaccharide exposure increased CD3 and myeloperoxidase-positive cells (p < 0.05). Repetitive exposure to lipopolysaccharide or combined Ureaplasma parvum & lipopolysaccharide exposure increased intestinal inflammation (p < 0.05). The reduction of nuclei of neurons was most significant with repetitive lipopolysaccharide exposures but could be detected in all other intervention groups compared to the control group. Astrocyte-like glial cells increased if exposure to lipopolysaccharide was only 2 days before delivery or chronic exposure to Ureaplasma parvum existed beforehand (p < 0.05). Discussion: After exposure to chorioamnionitis induced by Ureaplasma parvum and/ or lipopolysaccharide, inflammatory responses as well as structural changes of the enteric nervous system were more pronounced the longer and the more frequent the exposure to pro-inflammatory stimuli before birth. These changes may cause functional effects of clinical importance.